Socioenvironmental impacts of hydroelectric construction: A literature review (Research, Society and Development, 2024)
In this literature review a systematic analysis was made with the objective of identifying the main socio-environmental impacts resulting from the construction of hydroelectric plants. Despite their importance for the energy supply of the whole society, the problems generated by the implementation of hydroelectric plants are enormous and besides affecting the local biodiversity, they also interfere with the health of the populations living in the areas where such enterprises are installed. To this end, a bibliographic survey of scientific production was carried out through the CAPES, PubMed, and SciELO interfaces. A total of 289 articles were found, and after reading and defining selection criteria, 30 studies were selected for a more detailed review of the hydroelectric plants and their socio-environmental repercussions. As a result of the data collection the following categories of analysis were observed: environment, society, and health, in order to understand the challenges surrounding the construction of hydroelectric plants. From the information analyzed it can be concluded that if on the one hand the energy produced by a hydroelectric plant is considered clean, on the other it has a range of significant environmental, social and health effects, and that it is up to the managers of this business, the rational use of natural resources involved in the implementation of the hydroelectric plant, because only sustainable planning and execution can minimize these impacts.